The Cyclicality of the Stepping-Stone Effect of Temporary Agency Employment - Elke J. Jahn; Michael Rosholm (Institute of Labor Economics (IZA), 2018)
This paper investigates whether the stepping-stone effect of temporary agency employment varies over the business cycle. Using German administrative data for the period 1985-2012 and an estimation framework based on the timing-of-events model, we estimate in-treatment and post-treatment effects and their relationship to the aggregate unemployment rate. We find evidence of a strong lock-in effect of agency employment, particularly in tight labor markets. This suggests that firms do not use agency employment as a screening device when unemployment is low. Moreover, the positive post-treatment effect is noticeably larger in periods of high unemployment, indicating that workers might be activating networks they established while in treatment. We further document that the matching quality in terms of earnings improves for those leaving unemployment directly from agency employment. This gain is higher when unemployment is low.
Keywords: C41; J40; J64; 330; temporary agency employment; stepping-stone effects; cyclicality; Germany